Kristologi menurut Injil Yohanes [Christology According to the Gospel of John] - Ksatria Londong Patiung (Universitas Pelita Harapan, 2023)
The understanding of Christology is sometimes vague. Some think that Jesus only has the nature of God and does not have a human nature, while others think that Jesus is an ordinary human being. Therefore, believers must have a correct understanding based on the truth of God's Word. The Gospels testify about Jesus Christ and His ministry. This paper specifically explains Christology from the perspective of the Gospel of John with its uniqueness. The Gospel of John affirms the belief that Jesus is the Messiah and the Son of God (John 20:30-31). John emphasizes that Jesus has a special personal relationship with God that no one else has. In addition to affirming Jesus as the Messiah and the Son of God, John also affirms Jesus' recognition of Himself as the